Thermodynamic and Technological Studies of the Electric Smelting of Satpaevsk Ilmenite Concentrates; Metals; Vol. 14, iss. 11 - Myrzakulov M. Maksat; Dzhumankulova S. Saltanat; Barmenshinova M. Madina; Martyushev N. V. Nikita Vladimirovich; Skeeba V. Yu. Vadim Yurjevich; Kondratjev V. V. Viktor Viktorovich; Karlina A. I. Antonina Igorevna (2024, 2024)
Title screen